Analysis of Customer Behavior and Attitudes (General Risk) on Satisfaction, Trust and Halal Awareness of Purchase Intentions in Food Delivery Applications - Wulandari, Septi Aditya; Sari, Rianita Puspa; Hadining, Aulia Fashanah (JDM (Jurnal Dinamika Manajemen), 2023)
The COVID-19 pandemic in Indonesia has caused changes in people’s behavior, such as increased use of online shops, working at home (WFH), and other social activities carried out virtually or online. One of the policies in the era of the COVID-19 pandemic is social distancing or physical distancing, which causes people to keep their distance and avoid crowds to break the chain of the spread of COVID-19. In addition, the existence of social distancing or physical distancing policies has resulted in high product purchases online, one of which is product purchases in food delivery applications. Now, on the food delivery application is not policy regarding halal awareness so that purchasing products online makes customers see common risks such as health risks, psychological risks, environmental risks, social risks, quality risks, financial risks, and time-loss risk that affects customer trust, customer satisfaction, and purchase intention. The purpose of this study is to identify the factors of customer attitudes and behavior (general risks) that affect customer satisfaction and trust and the effect of awareness, satisfaction, and trust of halal awareness on the intention to buy halal products in food delivery applications.